Salmonella Enterica Diarozoniae Strain's Pattern of Increased Antibiotic Resistance - Askar, Esraa Fadhil; Al-karawi, Kawthar Kadhim; Salman, Khawlah Abdallah; Hussein, Hussein Ali (South Eastern European Journal of Public Health, 2024)
Salmonella enterica subsp. diarizonae is a bacterial strain that has been of amassed alarm due to its influence on community health. This bacteria is frequently isolated from cold-blooded reptiles, sheep and monkeys. Lately, it has been identified from birds migrating transversely the continent of Asia and Europe. This study is the first of its kind in Iraq to diagnose this serotype of Salmonella from chicken meat and study the level of its resistance to antibiotics. Ten types of antibiotics were used, and this bacteria was extremely unaffected to seven antibiotics out of a total of ten antibiotics and sensitive to only three, with an average diameter of inhibition of Tetracycline 10 mm and Chloramphenicol 7mm. Salmonella were used as a comparison sample, and this bacteria was sensitive to a large number of antibiotics notwithstanding its high resistance to antibiotics, according to a large number of research. The occurrence of antibiotic resistance in Salmonella enterica diarizonae additional confuses the controlling of infections and increases distresses about the efficiency of antibiotic treatment.